Fracture Toughness and Crack Resistance of Steam Pipeline Steel in Initial and Used States - Zrilic, M.; Burzic, Z.; Cvijovic, Z. (Проблемы прочности, 2004)
Premature fracture of steam pipelines from
14MoV6 3 steel designed for 1000,000 h service
life at 540°C has been studied. Test specimens are
manufactured from steel in the initial state and after
117 h of operation. Application of the local approach
to fracture and the metallographic analysis,
in addition to classical methods (tensile, crack resistance,
and fatigue strength tests), provided a
more precise evaluation of steel properties degradation
due to elevated temperatures and stresses.
Urgency of further development of the local approach
to predicting material fracture after
long-term operation at high temperatures has been
substantiated. Исследуется проблема преждевременного разрушения паропроводов (сталь 14MoV6 3) с
расчетным ресурсом 100 тыс. ч при температуре 540°С. При изготовлении экспериментальных
образцов использовалась сталь в исходном состоянии и после 117 тыс. ч эксплуатации.
Применение локального подхода механики разрушения и металлографического анализа
наряду с классическими методами (испытания на растяжение, трещиностойкость,
усталостную прочность) позволило более точно оценить деградацию свойств стали под
действием высоких температур и напряжений. Обоснована необходимость дальнейшего
развития локального подхода к прогнозированию условий разрушения материалов при длительной
эксплуатации в условиях высоких температур. Досліджується проблема передчасного руйнування паропроводів (сталь
14MoV6 3) із розрахунковим ресурсом 100 тис. год за температури 540оС. При
виготовленні експериментальних зразків використовувалася сталь у
первинному стані та після 117 тис. год експлуатації. Використання локального
підходу механіки руйнування і металографічного аналізу поряд із класичними
методами (випробування на розтяг, тріщиностійкість, міцність від
утомленості) дозволило більш точно оцінити деградацію властивостей сталі
під дією високих температур і напружень. Обгрунтовано необхідність
подальшого розвитку локального підходу до прогнозування умов руйнування
матеріалів при тривалій експлуатації в умовах високих температур.